The role management skills for the rewards system: study case of Alpha Multinational Company - Bastos, Fabrício César (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
The aim of this article is to analyze the role of management skills for the rewards system. Given this scope, it briefly articulates the state-of-art of these two themes. Initially we present the conceptual evolution of competences according to American and European schools. Then, the rewards, from the traditional to the strategic model that ended the parity of remuneration to displace the centrality of the position for individual performance. Thus, a study case of a multinational company named Alpha, which adopted this system. Subsequently, we sought to determine a possible alignment with management skills. In conclusion, we identified a mechanism for retaining talent and enabling self-development.